The third generation of e-learning: expansive learning mediated by a weblog. (30th May 2007) - Makino, Yukari
This study abandons the security system of an ID and password that creates an exclusive and encapsulated community. Instead, it aims to develop expansive learning in which vertical and horizontal developments are integrated into a single curriculum. The author has designed an activity system for expansive learning mediated by a weblog. For vertical development, students work on the construction of verbal and nonverbal messages. For horizontal development, they present their works to the public through a weblog and ask the anonymous audience for critical comments. This activity system includes the vertical accumulation of knowledge and skills and the horizontal movement of different communities across borders. It was implemented as part of a university seminar course in a 2005 pilot study. Based on the analysis of the implementation records, the outcomes and future development of the system will be discussed in terms of the vertical and horizontal developments.